Investigation of Twin Tunnel Deformation with Umbrella Grouting Protection & NATM Tunneling using 3D Finite Element: Case Study Cisumdawu Tunnel - Wellyanto Wijaya; Paulus Pramono Rahardjo; Aswin Lim (Kadiri University, 2021)
Cisumdawu Tunnel is a twin tunnel 472 m long located in Sumedang. Twin tunnel construction can cause additional ground settlement and tunnel deformation. The tunnel construction method used is the New Austrian Tunneling Method (NATM) and umbrella grouting protection system. The principle of NATM is to maximize surrounding soil capacity to support its weight and balance the stresses around the tunnel. Investigation of tunnel deformation is important to know tunnel structure behavior and avoid possible failure. This research aims to know tunnel deformation and the effect of twin tunnel construction on the deformation and ground settlement. The data used such as tunnel geometry, monitoring data, pressuremeter test, and the drilling test. The 3D analysis will be performed for a single tunnel and twin tunnel using Midas GTS-NX, and monitoring data will be used for verification analysis. The 3D FEM help to model the soil condition and construction stage according to the actual condition. The analysis results show the maximum tunnel deformation that occurs from the beginning of the tunnel construction is 12.64cm. If the deformation starts to be calculated following the monitoring reading time, after the excavation at the monitoring point, the maximum deformation of the analysis results is 3.3&4.4cm, where the monitoring shows maximum deformation of 3.3&4.3cm. Through the results, it can be said that the analysis using 3D FEM with pressuremeter test parameter represents actual conditions. Twin tunnel construction side-by-side increases ground settlement and lateral tunnel deformation significantly. Hence, it shows that tunnel analysis using 3D FEM recommends for future investigation of tunnel deformation.